INTERAZIONI FRA MICROPLASTICHE E BATTERI IN DUE SITI DEL MAR TIRRENO: LA CAMPAGNA SEA PLASTICS 2021 - Caruso, Gabriella; Alasonati, Enrica; Fisicaro, Paola; Domenek, Sandra; Vichot, Manon; Lovato, Helene; Corami, Fabiana; Azzaro, Maurizio; Papale, Maria; Lo Giudice, Angelina; et al. (Biologia Marina Mediterranea, 2024)
As a first contribute to assess the effect of the collection device and the sampling site on the plastisphere distribution and metabolism, in May 2021 microplastics (MPs) were collected at two coastal Tyrrhenian stations [Naples Gulf (NA) and Castelsardo (SAR)] from surface (using Niskin bottles and Manta net) and along the water column (0-16 m) using a WP2 Plankton net. A significantly higher abundance of MPs were collected by the Niskin bottle, which collected also those <100 µm. Conversely, microbial community showed the highest activity rates in the samples collected with Manta net. Significant differences in the abundance and metabolic properties of plastic-associated bacteria underlined that the collection device, rather than the sampling site, affects the plastisphere assemblage.